2022
DOI: 10.15585/mmwr.mm7132e4
|View full text |Cite
|
Sign up to set email alerts
|

Interim Guidance for Prevention and Treatment of Monkeypox in Persons with HIV Infection — United States, August 2022

Abstract: On August 5, 2022, this report was posted as an MMWR Early Release on the MMWR website (https://www.cdc.gov/mmwr).Monkeypox virus, an orthopoxvirus sharing clinical features with smallpox virus, is endemic in several countries in Central and West Africa. The last reported outbreak in the United States, in 2003, was linked to contact with infected prairie dogs that had been housed or transported with African rodents imported from Ghana (1). Since May 2022, the World Health Organization (WHO) has reported a mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
118
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(139 citation statements)
references
References 21 publications
3
118
1
1
Order By: Relevance
“…Recent reports have found that concurrent sexually transmitted infections were common in persons with monkeypox ( 3 , 7 ). Clinicians and health officials implementing monkeypox education, testing, and prevention efforts should also incorporate recommended interventions for other conditions occurring among gay and bisexual men, including HIV infection, sexually transmitted infections, substance use, and viral hepatitis §§ ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports have found that concurrent sexually transmitted infections were common in persons with monkeypox ( 3 , 7 ). Clinicians and health officials implementing monkeypox education, testing, and prevention efforts should also incorporate recommended interventions for other conditions occurring among gay and bisexual men, including HIV infection, sexually transmitted infections, substance use, and viral hepatitis §§ ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…Public health efforts should continue to ensure equitable access to monkeypox screening, prevention, and treatment, particularly among MSM. It is important that systems for delivering HIV and STI care and prevention be leveraged for monkeypox evaluation, vaccination and other prevention interventions, and treatment (10)…”
Section: Discussionmentioning
confidence: 99%
“…Despite being a mild and self-limiting disease in most cases, some conditions, such as immunosuppressive diseases, pregnancy and lactation, pediatric population, and people with a history of active exfoliative skin dermatoses may be associated with complications and worse prognosis 16 . These conditions may benefit from drugs approved for smallpox and cytomegalovirus treatment and which may have some activity against monkeypox virus, such as tecovirimat (approved treatment for smallpox) and cidofovir (approved treatment for cytomegalovirus) 17 .…”
Section: Discussionmentioning
confidence: 99%
“…In terms of pre- and post-exposure prophylaxis, there are two vaccines licensed by the Food and Drug Administration (FDA), USA, recommended primarily for people at risk of occupational exposure to orthopoxviruses, such as those working with diagnostic tests for monkeypox virus detection and now, as the multinational monkeypox outbreak continues, vaccines are also recommended for groups most at risk for acquiring severe monkeypox 17 . JYNNEOS is a live virus vaccine using non-replicating modified vaccinia Ankara (MVA) licensed for smallpox prevention and now, also for monkeypox in adults aged ≥ 18 years, being administered in two doses with 28 days interval 18 .…”
Section: Discussionmentioning
confidence: 99%